Injection of brown-coal tar in a statistical relationship with the significant parameters of a blast furnace - Pustějovská, Pavlína (Materiali in tehnologije, 2012)
The extremely large energy requirements of blast-furnace iron production and the high levels of pollution in terms of carbon dioxide have resulted in systematic efforts aimed at decreasing the specific consumption of fuels and deoxidizing agents during this process. This paper deals with the injection of alternative fuels into a blast furnace and their effect on the blast furnace's operation. In this case oil injection was replaced by coal-tar injection. A comparison analysis of the brown-coal generator tar injection and oil injection was applied to assess the effect of the injection on the reduction of COsub2 emissions. The daily parameters of the inputs and outputs were available. The statistical relations for the injection of brown-coal tar and the significant parameters of the aggregate are studied. Correlation coefficients indicating the tightness in the tar injection and other significant technological parameters, such as the specific coke consumption, theoretical combustion temperature and the emissions of the blast furnace are calculated.
Keywords: blast furnace; plavž; tar; katran; vbrizgavanje; injection